ENVIRONMENTAL DISCLOSURE DAN MITIGASI FINANCIAL DISTRESS: BUKTI KEBERLANJUTAN BISNIS PERUSAHAAN - Najmuddin, Ahmad Bebin; Sulistyawati, Ayu Sarah (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2025)
This research aims to analyze the impact of profitability and operating capacity on financial distress, with environmental disclosure serving as a moderating variable. The study focuses on non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2020–2024. A quantitative method was employed using the PLS-SEM approach, including both internal and external construct model testing. The findings reveal that both profitability and operating capacity negatively influence financial distress. Additionally, environmental disclosure significantly moderates the relationship between profitability and financial distress, but does not moderate the link between operating capacity and financial distress. These results highlight the role of environmental disclosure as an aspect of corporate social responsibility that can enhance a company’s financial stability and mitigate the risk of financial distress.Keywords: Environmental disclosure, financial distress, profitabilitas, operating capacity.